Application of carbon aerogel electrosorption for enhanced Bi2WO6 photoelectrocatalysis and elimination of trace nonylphenol. (January 2018) - Fan, Zhiyong; Shi, Huijie; Zhao, Hongying; Cai, Junzhuo; Zhao, Guohua
Abstract: Carbon aerogel (CA) was used in electrosorption to enhance Bi2 WO6 photoelectrocatalytic process for trace amount (1 mg/L) nonylphenol (NP) elimination. The composite Bi2 WO6 /CA electrode fabricated with CA as adsorbent and Bi2 WO6 as photocatalyst was found to be effective to achieve the synergy of electrosorption and photoelectrocatalysis. At alkaline pH (>12), more than 90% of NP was adsorbed by applying potential lager than 0.6 V ( vs. SCE), most of which was gathered on the electrode. Electrosorption was promoted with increasing of electric field intensity and pH. NP gathered on the electrode was degraded completely (99.3%) in the photoelectrocatalytic process due to electrosorption enrichment and well photocatalytic properties of the electrode. The degradation efficiency depended largely on the electrosorption process, thus the removal of NP was also affected by pH and applied potentials. The electrode achieved "self-cleaning" due to synergistic effect of electrosorption and photoelectrocatalysis: electrosorption was favorable for photocatalytic degradation and the photocatalytic degradation can renew the electrode after the adsorbed pollution was removed. Trace NP can be eliminated efficiently in real sample, and the final concentration of NP was below 6.4 μg/L, which meet the effluent standard of NP. Graphical abstract: Image 1